Branding the Street: Visual Politics in Zohran Mamdani’s 2025 New York City Mayoral Campaign - Dr. Syeda Arooj Zehra Rizvi (ACADEMIA International Journal for Social Sciences, 2025)
Political branding in contemporary urban democracies increasingly depends on visual communication strategies that embed identity within community experience rather than relying on standardized campaign aesthetics. This qualitative study examines the 2025 mayoral campaign of Zohran Mamdani, whose visual branding system adopted an unconventional visual language grounded in the material and cultural aesthetics of New York City’s working-class neighborhoods. On November 4, 2025, Mamdani won the mayoral election with 50.78% of the vote, achieving the highest voter turnout in over fifty years. By drawing from the city’s visual environment, including subway signage, bodega storefronts, taxicab colors, and multilingual community markers, the campaign positioned itself as locally rooted and culturally resonant. Employing semiotic analysis and multimodal discourse analysis within an interpretive framework, the study analyzes how the campaign achieved differentiation through saturated color palettes, hand-rendered typography, community-referential illustrations, and inclusive multilingual messaging. The findings demonstrate that these design choices constructed a coherent identity system that functioned as persuasive political communication, shaping voter perception, signaling ideological alignment, and cultivating trust through aesthetic authenticity. The analysis reveals that community-centered design, when applied to political branding, operates as a strategic mechanism for building solidarity, strengthening political positioning, and challenging conventional norms of campaign communication. This study contributes to scholarship on visual communication and political marketing by illustrating how graphic design can reshape democratic engagement when it emerges from local culture and shared urban experience.